The sequential mediating roles of self-esteem and life satisfaction in the relationship between health perception and perceived social status among college students - Eun Bee Kim; Jhong Yun Kim (Frontiers in Psychology, 2026)
Background College students face significant challenges in their physical and psychological well-being, potentially affecting their perception of social status. This study examines the association between health perception and perceived social status among college students and investigates the potential mediating roles of self-esteem and life satisfaction. Methods Data from 5,966 participants (50.8% female, 49.2% male) were analyzed from the 2016 Korean Education and Employment Panel Survey (KEEP). Analyses were conducted using SPSS 21.0, AMOS 22.0, and the PROCESS macro. The research model examined the direct relationships between health perception, self-esteem, life satisfaction, and perceived social status, as well as the potential mediating roles of self-esteem and life satisfaction. Results Health perception was positively associated with self-esteem ( β = 0.232, p < 0.001), life satisfaction ( β = 0.273, p < 0.001), and perceived social status (β = 0.120, p < 0.001). Self-esteem showed positive associations with life satisfaction ( β = 0.359, p < 0.001) and perceived social status (β = 0.078, p < 0.001). Life satisfaction was significantly related to perceived social status ( β = 0.419, p < 0.001). The indirect association of health perception with perceived social status through self-esteem was 0.018 (95% CI [0.011, 0.025]), through life satisfaction was 0.115 (95% CI [0.101, 0.129]), and through both mediators sequentially was 0.035 (95% CI [0.029, 0.041]). Conclusion Results suggest that college students’ health perception may be associated with their perceived social status both directly and indirectly through potential mediating roles of self-esteem and life satisfaction. Because these findings are based on cross-sectional secondary data, they represent statistical associations rather than confirmed causal mechanisms. Health awareness, self-esteem, and life satisfaction were associated with more positive perceived social status; however, longitudinal research is needed before implications for educational interventions can be drawn.